Consensus communication strategies to improve doctor-patient relationship in paediatric severe asthma - Antonietta Cappuccio; on behalf of Paediatric Sound Group; Filomena Bugliaro; Silvia Maria Elena Caimmi; Valeria Caldarelli; Lucia Caminiti; Enza D'Auria; Emanuela di Palmo; Marzia Duse; Alessandro Giovanni Fiocchi; Francesco Gesualdo; Ahmad Kantar; et al. (BMC, 2019)
Abstract Background Asthma is a chronic inflammatory disease that is very common among youth worldwide. The burden of this illness is very high not only considering financial costs but also on emotional and social functioning. Guidelines and many researches recommend to develop a good communication between physicians and children/caregiver and their parents. Nevertheless, a previous Italian project showed some criticalities in paediatric severe asthma management. The consensus gathered together experts in paediatric asthma management, experts in narrative medicine and patient associations with the aim of identify simple recommendation to improve communication strategies. Methods Participants to the consensus received the results of the project and a selection of narratives two weeks before the meeting. The meeting was structured in plenary session and in three working groups discussing respectively about communication strategies with children, adolescents and parents. The task of each working group was to identify the most effective (DO) and least effective practices (DON' T) for 5 phases of the visit: welcome, comprehension of the context, emotions management, duration and end of the visit and endurance of the relationship. Results Participants agreed that good relationships translate into positive outcomes and reached consensus on communication strategies to implement in the different phase of relationships. Conclusions The future challenges identified by the participants are the dissemination of this Consensus document and the implementation of effective communication strategies to improve the management of pediatric asthma.